Influence of the Chelating Solutions in the Resistance of Glass Fiber Posts to the Root Dentin - Marques, Eduardo Fernandes; Marceliano-Alves, Marília Fagury Videira; Pelegrine, Rina Andrea; Pinheiro, Sérgio Luiz; Bueno, Carlos Eduardo Da Silveira (European Journal of Dentistry, 2020)
Objective This study aimed to evaluate the influence of chelating agents (EDTA, citric acid and Tetraclean) on glass fiber posts adhesion to root dentin.Materials and Methods Forty mandibular premolars single canals, with complete apical root, straight, circular cross sections were selected, accessed and had the cervical third prepared with Gates-Glidden drills, then included in resin, instrumented with ProTaper Universal and the root canal obturation was carried out. After, the samples were randomly divided into 4 groups (n = 10) to test the final irrigation solutions: G1:17% EDTA; G2:10% citric acid; G3: Tetraclean and G4: saline solution (control). After 30 days of storage (36.5° C and 100% humidity), the post preparation was performed leaving 4 mm of apical endodontic filling. Then, a fiber-glass post previously selected was coated with ED Primer adhesive system and resin sealer Panavia, installed and stored for 24 hours at 37°C. The samples were subjected to a tensile test with a constant speed of 1 mm/min with 2000 Kgf. The results were analyzed with the ANOVA test.Results The statistical analyzes indicated no significant differences between the groups (p > 0.05).Conclusion The type of chelating agent used in the final irrigation of the endodontic treatment did not influence the tensile strength of the fixation system used to sealer the glass fiber posts to the intracanal dentin.
Keywords: chelating agents; dental posts; root canal irrigants